The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Toxicity of Heavy Metals to Legumes and Bioremediation 2012
DOI: 10.1007/978-3-7091-0730-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Heavy Metals on Germination and Physiological Processes of Plants

Abstract: Pollution of the environment by toxic metals in recent years has accelerated dramatically due to rapid industrial progress. Heavy metals when taken up in amounts in excess of the normal concentration produce lethal effects on plants, on microbes, and directly or indirectly on the human health. Deleterious impact of metals on plants includes the reduction in germinability of seeds, inactivation of enzymes, damage to cells by acting as antimetabolites, or formation of precipitates or chelates with essential meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 128 publications
1
12
0
1
Order By: Relevance
“…According to Hagemeyer (1999), roots that directly interacted with nutrient and toxic elements, were generally more sensitive than other tissue of plants. Wani et al (2012), also reported that the root of the various plants including cereals was the first organ that was directly exposed to metal in soil and hence was the target of stressor molecules including heavy metals. Diwan et al (2010) used the root growth as an important parameter in classifying heavy metal tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hagemeyer (1999), roots that directly interacted with nutrient and toxic elements, were generally more sensitive than other tissue of plants. Wani et al (2012), also reported that the root of the various plants including cereals was the first organ that was directly exposed to metal in soil and hence was the target of stressor molecules including heavy metals. Diwan et al (2010) used the root growth as an important parameter in classifying heavy metal tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…At the cellular and molecular levels, heavy metal toxicity affects plants in many ways. For instance, it alters the key physiological and biochemical processes such as seed germination, pigment synthesis, photosynthesis, gas exchanges, respiration, inactivation and denaturation of enzymes, blocks functional groups of metabolically important molecules, hormonal balance, nutrient assimilation, protein synthesis, and DNA replication (Nagajyoti et al, 2010 ; Yadav, 2010 ; Keunen et al, 2011 ; He et al, 2012 ; Hossain et al, 2012a , b ; Silva, 2012 ; Wani et al, 2012 ; Singh et al, 2013 ). Under Cd stress, severe deleterious effects on various photosynthetic indices such as photosynthetic rate (Pn) and intracellular CO 2 concentration (Ci) have been reported in tomato seedlings (Dong et al, 2005 ).…”
Section: Plant Responses To Heavy Metal Stressmentioning
confidence: 99%
“…A trace level of many heavy metals is required for the activation and/or functioning of many enzymes and co-enzymes during anaerobic digestion (Mata-Alvarez et al 2000;Bayer et al 2007;Cirne et al 2007). This is mostly due to the chemical binding of heavy metals to the enzymes and microorganisms (Brady and Duncan 1994), resulting in the disruption of enzyme structure and activities (Li and Fang 2007;Wani et al 2012). In relatively high concentrations, they can form unspecific compounds, creating cytotoxic effects (Kavamura and Esposito 2010) and altering the optimum biochemistry and performance of the processes.…”
Section: Heavy Metals and Biochemical Reactionsmentioning
confidence: 99%